Influence of risk factors on the safety of ileocolic anastomosis in Crohn's disease surgery. - Tzivanakis, A; Singh, J; Guy, R; Travis, S; Mortensen, N; George, B (2012)
Ileocecal resection is the most commonly performed operation in patients with Crohn's disease. Anastomotic-associated complications, with their associated morbidity, are the most feared risks of surgery. This study aimed to assess the influence of a variety of putative risk factors in a homogenous group of patients undergoing first or subsequent surgery for Crohn's disease to quantify the cumulative risk for anastomotic-associated complications. All patients undergoing ileocecal or ileocolic resections for Crohn's disease from 2000 to 2010 were studied with the use of a prospective database. Demographics, operative details, possible risk factors, and anastomotic-associated complications were recorded. Patients having strictureplasties, multiple resections, or subtotal colonic resections were excluded from analysis. Statistical analysis was by univariate analysis (Mann-Whitney U test) and binary logistic regression. An anastomotic-associated complication was defined as a proven anastomotic leak, postoperative fistulation, or intra-abdominal abscess formation. Two hundred seven patients (109 female) with a median age of 35 years (range, 13-75 years) were identified. One hundred seventy-three underwent primary anastomosis, 94 as an emergency procedure. Fifty-three had laparoscopic (5 converted) procedures. Nineteen of 173 anastomotic complication events (11%) were recorded. Steroid usage (OR 2.67, 95% CI 1.0-7.2) and the presence of preoperative abscess formation (OR 3.4, 95% CI 1.2-9.8) were identified as independent predictors of anastomotic-associated complications. In the absence of both steroids and intra-abdominal abscess, the risk of anastomotic complications was 6%, which increased to 14% if either risk factor was present. When both risk factors were present, complication rates reached 40%. Steroid usage and preoperative abscess were associated with higher rates of anastomotic complications following ileocolic resection for Cohn's disease. When both risk factors are present, it is best to avoid primary anastomosis.